A Modern Approach to Comprehensive Competitive Potential Assessment for Service Providers - R. Zakirova, Irina; G. Zainasheva, Zarima; F. Shaikhutdinova, Gulnara; U. Ibragimova, Nuriya; N. Korotkova, Lyudmila; D. Mukhametova, Diana; ., . (International Journal of Engineering and Technology, 2018)
The relevance of the research is determined by specifics of competitive potential assessment for service providers. The purpose of this research is a comprehensive competitive potential assessment (CCPA) of Russian service providers, including an identification of their competitive positions in the market, as well as opportunities and problems areas in their operational activities to facilitate further management decisions. The paper proposes a methodical toolkit to assess competitive potential of a service provider. Based on the presented technique, a comprehensive competitive potential analysis of the following communications service providers (CSP) has been carried out: MTS PJSC, MegaFon PJSC; VimpelCom PJSC. The following of competitive potential components have been researched: resource, labour, organizational and managerial, innovative, marketing, service and technological. As the result, the potential competitiveness integral indicators calculated for the CSPs have shown the following values: MegaFon PJSC – 36%, MTS PJSC – 35%, VimpelCom PJSC – 29%. The conclusions section of this work contains recommendations on increasing the competitive opportunities of the CPS as well as a substantiation of the practical importance of the presented technique in implementing management technologies for diagnostics of the development of service industries in various sectors of the national economy, including companies of the oil and gas sector. The materials of the article can be useful for managers of service companies and service consumers.